Cost Contingency Strategies in Building Construction: Evaluating Project Risk Influence - Putri Suci Mawariza; Michella Beatrix (Universitas Islam Raden Rahmat, Malang, 2024)
Contingency costs are an important part of construction to achieve successful project management. In determining contingency costs, practitioners have used a very subjective approach. This study discussed the determination of the contingency cost of high-rise buildings in six research object projects, based on the results of risk evaluation. The risk evaluation used in this paper is based on the risks in the construction phase. The method used to know the relationship between risk and contingency costs is simple linear regression with tools. The results of this study indicate that the greater the level of risk, the greater the contingency costs incurred by the project. the risk level contributed 71.6% to the contingency cost, while the rest was influenced by other factors. The equation formed is, that if the risk increases by 1 unit, the total contingency cost will increase by 0.0916 units.